Occurrence of selenium-containing tRNAs in mouse leukemia cells. - Ching, W M (1984)
Selenium incorporation into the polynucleotide structures of tRNAs has been documented in several microorganisms. In the present study, selenium-containing species were isolated from bulk tRNA preparations from 75Se-labeled mouse leukemia cells. The major 75Se-labeled species was similar in size and exhibited the same sensitivity to ribonuclease as did Escherichia coli tRNAs. The chromatographic properties of the intact major selenium-containing tRNA species indicated it to be very hydrophobic in character. The selenium component that is unstable at neutral-to-alkaline pH but is relatively stable at acid pH is not an esterified selenoamino acid. HPLC analysis of enzymic digests of the major selenium-containing species detected selenium-containing hydrophobic products (probably selenonucleosides ). These properties strongly suggest that the selenium in the mouse leukemia-cell tRNAs is present in the form of a selenium-modified nucleoside.